EKSPLORASI AKTINOMISET SEBAGAI PENGHASIL ANTIBIOTIKA DARI TANAH MANGROVE Sonneratia caseolaris DI TANJUNG API API - Awalul Fatiqin (Biota, 2015)
Actinomycetes are soil organisms that have traits that are common to bacteria and fungi but also have quite different characteristics that limit into one group which is distinctly different. Study aimed to explore the mangrove actinomycetes from soil and tested the antibacterial potency. Soil samples taken from the mangrove land at Tanjung Api-api mangrove species Sonneratia caseolaris. Activity test antibacterial using a method modified disk a test bacterium Escherichia coli. Identification isolates of actinomycetes by observing the character of macroscopic colonies, microscopic conidia. The results showed that the obtained three different actinomycetes isolates, 1 isolate has the most potential ability to inhibit bacterial growth test with an average value of 1:13 cm in inhibiting the bacteria Escherichia coli.